HUBUNGAN KADAR DDIMER DENGAN AWITAN GEJALA DAN LAMA PERAWATAN PADA PENDERITA CEREBRAL VENOUS SINUS THROMBOSIS DI RSUP DR HASAN SADIKIN BANDUNG - Lisda Amalia,* Adnin Nugroho* (NEURONA, 2020)
INTRODUCTIONCEREBRAL VENOUS SINUS THROMBOSIS CVST IS ONE OF A CEREBROVASCULAR DISEASE WITH A DIVERSE AND ELUSIVE CLINICAL PRESENTATION DIAGNOSIS IS OFTEN CHALLENGING DUE TO LIMITATION IN DIAGNOSTIC TOOLS COAGULATION DISORDER IS ONE OF THE RISK FACTOR FOR CVST THAT CAN BE SEEN FROM DDIMER LEVEL WHICH TENDS TO INCREASE IN CVST PATIENTS